Rheological Characteristics and Proximate Principles of Sorghum Flour and Sorghum Bran for Possible Use in Baking - Osibanjo , A. A.; Ibidapo , P. O.; Ogunji , A. O.; Elemo , G. N. (European Journal of Applied Sciences, 2021)
The quality of sorghum flour and sorghum bran was evaluated in terms of the rheological properties and proximate composition compared with cassava flour, wheat flour and wheat bran at different levels of combination. Results show that sorghum flour seems comparable with cassava flour, as composite with wheat and hence can be a suitable alternative, particularly in non-cassava growing areas. The 50/50 wheat bran/sorghum flour appears to be promising and can be further explored in making whole grain bread. Sorghum bran also seems promising as an alternative to wheat bran and can be recommended for use in baking. In addition, its rich protein and fibre contents can be explored in novel, fibre-rich functional food formulations as well as in animal feed.